Understanding business research - Weathington, Bart L; Cunningham, Christopher J. L; Pittenger, David J (John Wiley & Sons, 2012)
Explore the essential steps for data collection, reporting, and analysis in business research Understanding Business Research offers a comprehensive introduction to the entire process of designing, conducting, interpreting, and reporting findings in the business environment.